8z+-2=3z+6

Simple and best practice solution for 8z+-2=3z+6 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 8z+-2=3z+6 equation:


Simplifying
8z + -2 = 3z + 6

Reorder the terms:
-2 + 8z = 3z + 6

Reorder the terms:
-2 + 8z = 6 + 3z

Solving
-2 + 8z = 6 + 3z

Solving for variable 'z'.

Move all terms containing z to the left, all other terms to the right.

Add '-3z' to each side of the equation.
-2 + 8z + -3z = 6 + 3z + -3z

Combine like terms: 8z + -3z = 5z
-2 + 5z = 6 + 3z + -3z

Combine like terms: 3z + -3z = 0
-2 + 5z = 6 + 0
-2 + 5z = 6

Add '2' to each side of the equation.
-2 + 2 + 5z = 6 + 2

Combine like terms: -2 + 2 = 0
0 + 5z = 6 + 2
5z = 6 + 2

Combine like terms: 6 + 2 = 8
5z = 8

Divide each side by '5'.
z = 1.6

Simplifying
z = 1.6

See similar equations:

| 3/4w-1/8=9/16 | | 3y^2-3u^4y^2=0 | | log(9x+6)=1 | | 23423=x^2+35x+30 | | 5(5x+1)=3x-8x | | 8x^2-5x+k=0 | | 4(w-1)=4 | | -325+75=t | | -[(2x+1)-5(x-4)]+4=10(x+3) | | 5=-5v+8 | | 2.5n-(-10)= | | 2x^2-4x-132=0 | | 2y+5x=-6 | | 86+(38+x)(2)= | | 6x^2=-72x | | -13-4=n | | X-6=-5whatisx | | 8-7n=57 | | x=-432 | | 6x-2yi=6+8i | | -5-2x=15 | | 22s=11s^2 | | 3b-5b=4 | | 125=5x-7(2x+5) | | 6x+3+7x+-12=180 | | s=-16t^2+64t | | 2x+20=2x | | 8y=x+8 | | -16=-n-8 | | 3(10-5)= | | 20x-39=15x-39 | | 12x-27=3x |

Equations solver categories